Reflectors Used To Raise the Efficiency of Solar System: Enhancing Solar System Efficiency with Reflectors (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Flat-roofed urban buildings bake in the sun all day with no shade from trees, so they are the perfect place for solar panels. They can deliver power directly to where it’s needed without significant transmission loss. But roof space is limited so efficiency is very important.Reflectors can be situated at an optimum angle to gain the greatest possible level of sunlight that can be achieved onto the panel .Conventional solar systems connect panels with a series string — and just like the old Christmas lights, the whole string goes dark if a single light is bad. Series associated sun powered cells have a similar issue and more awful A tree or cloud shadow, a fallen leaf, or crap of flying creature crap can lessen the yield of the entire string. In the event that the cells are not coordinated and similarly enlightened, effectiveness drops fundamentally.